The perfect suspension of work in the COVID-19 times. An alternative or employer abuse? - Torres Cadillo, Rosa Isabel (2020)
The pandemic produced by COVID-19 put the world up against a wall. As a result, the health crisis forced all governments to implement restrictive measures, such as mandatory confinement (quarantine), suspension of some fundamental rights, temporary suspension of several economic sectors that seriously damaged the economy, to the point that many businesses closed and they were forced to lay off workers, among others. In view of this, the Peruvian government implemented some alternative measures to guarantee labour rights, such as the perfect suspension of work —through which the labour link between employer and worker is maintained— or also the economic reactivation by stages and other benefits such as Reactiva Peru.